Transformasi pendidikan abad 21: implementasi deep learning dalam sistem pembelajaran digital di Sekolah Dasar - Rizky Arianty; Irma Sofiasyari; Rika Yuliana; Isna Amanaturrakhmah; Nunung Nurjanah (COLLASE (Creative of Learning Students Elementary Education), 2026)
The transformation of education in the 21st century demands the integration of advanced technologies, including Artificial Intelligence (AI), into learning systems. One branch of AI with great potential to revolutionize the way students learn is Deep Learning. This technology enables digital systems to automatically adjust learning materials according to individual needs and abilities, making the learning process more adaptive, personalized, and relevant. In realizing meaningful learning through digital education integrated with the concept of Deep Learning, it is essential to identify the components that must be considered. This study aims to examine the application of Deep Learning in digital learning at elementary schools and its impact on learning effectiveness. Using a descriptive qualitative approach, the study was conducted through literature review and preliminary observations of several AI-based platforms. The findings indicate that Deep Learning plays a significant role in providing interactive learning experiences, assisting teachers in identifying students’ difficulties in real time, and supporting learners with special educational needs. Nevertheless, implementation faces challenges such as limited school infrastructure and low levels of teachers’ digital literacy. Therefore, the successful integration of Deep Learning requires comprehensive support, including teacher training, data protection policies, and investment in technological facilities. Through a holistic approach, Deep Learning can become an essential part of transforming primary education to be more inclusive, sustainable, and responsive to the demands of the digital era.